2017
DOI: 10.15241/cmy.7.4.318
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Experiential Learning Through an Abstinence Assignment Within an Addictions Counseling Course

Abstract: This interview is the second in the Lifetime

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This finding informs clinics that training in empathetic understanding is essential for counsellors to improve relationships with clients. Experiential learning techniques, such as improvisation, role play, and abstinence or behaviour change challenges, can be used to teach empathy to counsellors and students (Bayne & Jangha, 2016;Giordano, Stare, & Clarke, 2015;Warren, Hof, McGriff, & Morris, 2012;Yates, DeLeon, & Rapp, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This finding informs clinics that training in empathetic understanding is essential for counsellors to improve relationships with clients. Experiential learning techniques, such as improvisation, role play, and abstinence or behaviour change challenges, can be used to teach empathy to counsellors and students (Bayne & Jangha, 2016;Giordano, Stare, & Clarke, 2015;Warren, Hof, McGriff, & Morris, 2012;Yates, DeLeon, & Rapp, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants' initial skepticism about the assignment as well as their assumptions that they had more willpower than an addict and the shifts in those perceptions after engaging in the activity speak to the need for experiential activities such as this to promote professional competence in undergraduate human services education. Yates, DeLeon, and Rapp (2017) found equivalent results by qualitatively analyzing "good-bye letters" to participants' substances of choice, journal entries, and reflection summaries by 17 counselor trainees who engaged in their abstinence project. Based on the results of the current study, similar studies conducted at the master's level, and earlier research on the benefits of experiential learning (Schelbe et al, 2014;Griffith & Frieden, 2000;Ziomek-Daigle, 2017), undergraduate programs may need to consider modifying their pedagogical approaches to addiction training so opportunities for lived experiences followed by reflection are integrated throughout the curricula to promote professional development.…”
Section: Implications and Future Directionsmentioning
confidence: 94%
“…Previous research (Caldwell, 2007;Giordano et al, 2015;Harrawood et al, 2011;Ieva et al, 2009;Spaid & Squires, 2006;Warren et al, 2012;Yates et al, 2017) showed the importance of experiential learning activities for graduate-level trainees to develop personally and professionally. The outcomes of the present study show how experiential learning activities can contribute to personal growth, development, and academic understanding for undergraduate substance disorder trainees.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Several authors promoted use of reflective writing practices within the context of experiential learning (Woodbridge & O’Beirne, 2017; Ziomek‐Daigle, 2017). Finally, contributions included qualitative exploration of an abstinence project within an addictions course (Yates, DeLeon, & Rapp, 2017), a Cultural De‐Centering Activity‐Visual in a multicultural course (Shiflett, McAuliffe, & Deaver, 2017), and an international videoconference exchange (Meekums, Wathen, & Koltz, 2017).…”
Section: Teaching and Trainingmentioning
confidence: 99%